PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN GURU - Irma Andesmiyanti; Osa Juarsa (Manajer Pendididikan, 2020)
This study described the role of principal to improving teacher’s discipline. The problems in this research was the role of principal to improve teacher’s discipline at SMAN 1 Bengkulu Tengah. The method of this research was descriptive approach. The subjects of this research were the principal, and eighteen subject teacher. The Data’s were collected through interviews, observations, and documentations. Data analysis was included data collection, reductioning data, display datato know how the role of the principals to improving teacher discipline 1 Bengkulu Tengah, Bengkulu Province. At last the research could be conclude that the role of the principals toimproving teacher’s discipline wouldl also increase the students discipline at SMAN 1 Bengkulu Tengah.The role of the principal toimproving teacher discipline could be attributed to the principal's role as manager, leader, motivator, and supervisor. The example of the principal that has been applied by the headmaster of SMA Negeri 1 Bengkulu Tengah it has been referring to the discipline indicator namely objectives and abilities, leadership examples, compensation, firmness, employee loyalty. It has also referred to the indicators of the principal's leadership of mobilizing, directing, motivating and supervising.